PERIDUCTAL STROMAL SARCOMA - Haluk Recai Ünalp; Taner Akgüner; Erdinç Kamer; Seyran Yiğit; Mehmet Ali Önal (European Journal of Breast Health, 2007)

(untitled)
Malignant mesenchymal tumours of the breast are rare neoplasms, and their incidence varies from 1%-3% of all malignant breast tumours. Periductal stromal sarcoma of the breast which a rare subgroup of malignant mesenchymal tumours is an extremely uncommon tumour. Excision of tumor with a negative margin is the primary modality in treatment of periductal stromal sarcoma of the breast. The role of radiotherapy and chemotherapy is still controversial in these patients.We report herein the case of a 52-year-old women in whom a periductal stromal sarcoma of the breast was managed with breast preserving surgery without radiotherapy or chemotherapy. No localy recurrence or metastasis was detected in the patient during sixteen months follow-up.